Peningkatan Kemampuan Mengenal Huruf Vokal Melalui Permainan Kartu Huruf Pada Perserta Didik Tunagrahita Kelas II SD di SLB Negeri Karanganyar - Rifdah Nurul Hayyah; Mahardika Supratiwi; Tri Endah Kurniyati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
Early literacy is a fundamental skill for academic success, especially in students with intellectual disabilities who often struggle to recognize letters and associate them with their sounds. This classroom action research aims to improve the ability to recognize vowel letters using letter card games among second-grade students with intellectual disabilities at SLB Negeri Karanganyar. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. The instructional media used was a set of vowel letter cards featuring symbols and familiar objects starting with the respective vowel sounds. The results showed a significant improvement in students’ ability to recognize vowel letters. The average score increased from 51.75% in the pre-cycle to 63% in cycle I and 87.25% in cycle II, reaching the “very good” category. The findings support the effectiveness of multisensory, interactive, and contextual learning through card games in increasing motivation, participation, and early literacy skills. This method also fosters a positive learning environment that promotes collaboration and emotional engagement. The results of this study provide practical recommendations for inclusive education practitioners to apply innovative and student-centered literacy strategies.